2019
DOI: 10.1111/ocr.12348
|View full text |Cite
|
Sign up to set email alerts
|

The effect of altered head and tongue posture on upper airway volume based on a validated upper airway analysis—An MRI pilot study

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Therefore, together with facial deformities, there are other variables such as subjects' BMI (body mass index) and height that influence the airway volume [ 33 ]. Changes in the position and craniocervical angle modify the airway volume and the position of the hyoid bone, which is an important variable to be considered when analysing the data [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, together with facial deformities, there are other variables such as subjects' BMI (body mass index) and height that influence the airway volume [ 33 ]. Changes in the position and craniocervical angle modify the airway volume and the position of the hyoid bone, which is an important variable to be considered when analysing the data [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the upper airway analysis, the primary confounding factors during 3D radiographic image acquisition include the individual's body, head, jaw, and tongue position, as well as the respiratory phase [5,14,15]. A systematic review on the effect of head and tongue posture on the dimensions and morphology of the pharyngeal airway concluded that altered head, body, and jaw position had a significant effect on the upper airway dimensions, particularly on the retro-palatal and retro-glossal regions of the oropharynx [14].…”
Section: Plos Onementioning
confidence: 99%
“…Over the past decades growing awareness of the detrimental effects of obstructive sleep apnea (OSA) has increasingly raised interest in morphometric evaluation of the upper airway [1][2][3]. Traditionally, upper airway morphology imaging consisted of a two-dimensional (2D) lateral cephalogram [4,5]. However, due to the technical advancement of computed tomography (CT), this imaging modality has gained increasing popularity [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations